Molecular Mechanisms of the Biological Control of Pine Wilt Disease Using Microorganisms - Xiaotian Su; Yimou Luo; Jingfei Hu; Yixin Xia; Min Liu; Yongxia Li; Haihua Wang (Microorganisms, 2025)
Pine wilt disease (PWD), caused by the pine wood nematode (PWN, Bursaphelenchus xylophilus), poses a significant threat to global pine forests and calls for the development of innovative management strategies. Microbial control emerges as an effective, cost-efficient, and environmentally sustainable approach to eliminate the damage from PWD. This review consolidates molecular mechanisms in the microbiological control of PWD, which focus on three core strategies: microbial control activity against PWN, biological control of vector insects, and the enhancement of host tree resistance to nematode infections. The review thoroughly evaluates integrated control strategies in which microbial control is used in traditional management practices. Recent studies have pinpointed promising microbial agents for PWN control, such as nematophagous microorganisms, nematicidal metabolites, parasitic fungi that target vector insects, and microbes that boost plant resistance. In particular, the control potential of volatile organic compounds (VOCs) produced by microorganisms against PWN and the enhancement of pine resistance to PWN by microorganisms were emphasized. Moreover, we assessed the challenges and opportunities associated with the field application of microbiological control agents. We emphasized the feasibility of multi-strategy microbial integrated control, which provides a framework for future studies on microbial-based PWD control strategies.